Development of a high-rate anaerobic bioreactor for energy production from rice-mill effluent - JOEJOE L. BOVAS; Dr, Shaji James P (Guide) (Tavanur 2009 Department of Farm Power, Machinery and Energy)
Development of a high-rate anaerobic bioreactor for energy production from rice-mill effluent
Development of a high-rate anaerobic bioreactor for energy production from rice-mill effluent